Epidemiological Study of Suspected Occurrence of Foot and Mouth Disease in Lamongan Regency - Sudarsono, Rahendra Prasetya Eko (Journal of Basic Medical Veterinary, 2022)
Lamongan is the epicenter of aphtae epizootica disease. Symptoms of the disease appeared from the newly purchased cattle in Balungpanggang District, Gresik Regency. Symptoms that appear hypersalivation, decreased appetite, panting, slightly feverish body temperature. This review was conducted by collecting primary data through field observations and supported by references from the Google Scholar database with the keywords foot and mouth diseases, aphtae epizootica and infectious diseases. The pattern of distribution is mainly cattle traffic, weak biosecurity in cattle pens and livestock transportation means for sending cattle from or to the animal market. Based on a descriptive analysis of the results of surveillance, investigation and sample testing indicating an outbreak of an infectious disease suspected to be FMD in Lamongan Regency according to the definition of an outbreak according to Law No. 18 of 2009 concerning Livestock and Animal Health and Government Regulation No. 47 of 2014 concerning Disease Control and Prevention. Animal. The direct impact in the form of economic losses due to illness and death if the outbreak is not controlled is estimated to be quite significant.